Late-Stage Transformation of Carboxylic Acids to N-Trifluoroethylimides with Trifluoromethyl Diazomethane - Qiu, Xiao-Feng; Liu, De-Yong; Zhang, Wen-Feng; Hu, Xiang-Guo (Synthesis, 2021)
We report the first systematic evaluation of the reaction of trifluoromethyl diazomethane (2,2,2-trifluorodiazoethane, CF3CHN2) with drug-like molecules. We found our previous copper-catalyzed transformation of carboxylic acids to the corresponding N-trifluoroethylimides with CF3CHN2 and acetonitrile is well-suited for the late-stage modification of drug and drug-like acids. A procedure that enables the use of solid nitriles and nitriles with high boiling points as viable substrates is also disclosed.
Keywords: N-trifluoroethylimides; trifluoromethyl diazomethane; late-stage functionalization; fluoroalkyl; copper; trifluoromethyl; 2,2,2-trifluorodiazoethane